Biological sex variation in bone mineral density in the cranium and femur. Issue 4 (July 2018) - Paschall, Anna; Ross, Ann H.
Abstract: Objectives: Sex and age trends in bone mineral density (BMD) play an important role in the estimation of age-at-death (AAD) of unidentified human remains. Current methodologies lack the ability to precisely estimate age in older individuals. In this study, BMD of the cranium and femur measured by DXA were examined to establish their applicability for age estimation in older adults. BMD as measured by DXA, is most commonly used clinically for prediction of osteoporotic fracture risk. We hypothesized that weight-bearing and non-weight-bearing bones, the femur and cranium, respectively, would provide valuable insights for aging. Methods: The sample consists of 32 sets of excised cranial fragments from the Regional Forensic Center, Johnson City, Tennessee and 41 associated crania and femora from the North Carolina Office of the Chief Medical Examiner. All crania and femora were scanned using a Hologic (R) DXA scanner and data were analyzed using Student t -tests, Loess regression, and ANOVA. Results: Student t -tests indicate a significant relationship between the sexes and cranial BMD and a significant relationship between age cohorts and femoral neck BMD. The Loess regression showed different aging patterns in the cranium for females and males older than 55. And the ANOVA showed changes in femoral neck after age 55. Conclusions: These results indicate age and sex dependent changes in BMD especially for individuals over the age of 55, which offers improvement from current aging methods for older individuals. Further research using a larger sample size could improve the predictive capabilities of the model. Highlights: Age and sex related changes in BMD of weight/non-weight bearing bones examined. BMD of weight-bearing bones provide insight for age estimation. BMD of non-weight bearing bones provide insight for sex estimation. Thickness measures are not a proxy for density estimation. Femoral BMD not sexually dimorphic; sex-dependent trends in cranial BMD provided.